Animal symbols of the deities of the Arabian Peninsula during the first millennium BC: Comparative Study - Al-Shouikan, Shahad Abdullah (Journal of Humanities & Social Sciences, 2022)
This research aimed at study the animal symbols of the deities of the Arabian Peninsula as it appeared through the research to identify the ancient man’s view of the attributes and characteristics of some animals that made him link them with the deity, and the reason for choosing the animal symbol for the deity, as we find that the symbols of the deities were animals from the same human environment. In southern Arabia, the bull, the ibex and the snake appeared at the forefront of the animal symbols due to the similarity between their characteristics and the characteristics of the lunar deities. These symbols took a high place in the religion of the kingdoms of southern Arabia, while statues of eagle and lion were found in abundance in the symbols of solar deities in the north of the Arabian Peninsula and as a symbol for some immigrant deities, which showed that the north of the Arabian Peninsula was affected by the deities of neighboring civilizations and the animal symbols turned into human statues.